An Empirical Study of Marketing Mix as a Satisfaction Tool in Modern Sport Administration in Ghana - Theophilus Ampah, Isaac (British Journal of Marketing Studies, 2016)
This paper aimed at (i) finding the extent of marketing mix adoption among sport institutions (ii) investigating the factors which prevent successful implementation of marketing mix by sport institutions (iii) identifying whether marketing mix adoption really leads to sport customers’ satisfaction (iv) highlighting any other findings which are relevant and can contribute towards effective marketing mix adoption by sport institutions in Ghana. The research took place in Takoradi Polytechnic, School of Business Studies, Department of Marketing. From October- 2015-Decemeber 2015. Structured self-completed questionnaires, journal, internet, books and Sport ministry of Ghana manuals were methodology used to collect data. 450 respondents from five main sport disciplines, sport stakeholders’ groups and Ghanaian sport customers were purposively selected. Data was analyzed using frequencies, mean, standard deviation, squared multiple correlation and cronbach alpah. 12 board members, 25 Chief executive officers, 30 Operating managers, 40 Coaching managers and 93 Other sport officials (Sport administration) and 146 sport customers, 24 sport sponsors, 30 sport development members, 25 sport advocate and 25 other sport stakeholders (Sport stakeholders) were sampled from 10 million Ghanaian sport customers (18 years and above and of sound mind). Source-Ministry of Youth and Sport, Ghana. Summary of views of respondents (Sport administrators) about marketing mix as a satisfaction tool on Likert scales ( 1=strongly disagree, 2 = disagree, 3= neutral, 4= agree and 5 strongly agree) is medium. Also, from Sport stakeholders’ perspective effectiveness of marketing mix adoption among sport institutions is medium. The study concluded that marketing mix adoption among sport institutions in Ghana is medium and also its usage as a satisfaction tool is effective for Sport administrators and ineffective for Sport stakeholders. Furthermore, it was discovered that the 7ps (product, price, promotion, place, people, process and physical evidence.) on their own are not enough to satisfy sport customers’ needs/wants